Antecedents of Knowledge Sourcing and Reuse from a Knowledge Repository in the Virtual Product Prototyping: The Role of Knowledge and System Quality Dimensions. (April 2016) - Filieri, Raffaele; Willison, Robert
Abstract : Knowledge has been identified as one of the most critical resources for achieving innovation and competitive advantage. Knowledge management systems (KMS) are, therefore, being adopted by companies to enhance knowledge management (KM) processes and innovation. Because most of new products projects are not "clean‐sheet" efforts, rather incremental redesigns of existing products, R&D people often retrieve and reuse existing knowledge to solve recurring problems in the prototyping of new products. Thus, knowledge sourcing and reuse are particularly important in this product development process. In the present research we investigated the antecedents of knowledge sourcing and knowledge reuse from an electronic repository. Predictions were tested in the context of the virtual vehicle prototyping process with data from 121 respondents of a large European Automotive supplier of R&D. Results provide support that knowledge accuracy, knowledge format, and knowledge completeness are strong predictors of knowledge reuse. While system integration, flexibility, and response time are considered strong determinants of knowledge sourcing in KMS. The study develops and tests a new model for measuring KMS success in the context of virtual product prototyping. Copyright © 2016 John Wiley & Sons, Ltd.